Dengue in Western Uganda: a prospective cohort of children presenting with undifferentiated febrile illnes - Boyce, Ross M.; Collins, Matthew; Muhindo, Rabbison; Nakakande, Regina; Ciccone, Emily J.; Grounds, Samantha; Espinoza, Daniel; Zhu, Yerun; Matte, Michael; Ntaro, Moses; Nyehangane, Dan; Juliano, Jonathan J.; et al. (BMC infectious diseases, 2020)
Background: The spatial distribution and burden of dengue in sub-Saharan Africa remains highly uncertain, despite high levels of ecological suitability. The goal of this study was to describe the epidemiology of dengue among a cohort of febrile children presenting to outpatient facilities located in areas of western Uganda with differing levels of urbanicity and malaria transmission intensity. Methods: Eligible children were first screened for malaria using rapid diagnostic tests. Children with a negative malaria result were tested for dengue using a combination NS1/IgM/IgG rapid test (SD Bioline Dengue Duo). Confirmatory testing by RT-PCR was performed in a subset of participants. Antigen-capture ELISA was performed to estimate sero-prevalence. Results: Only 6 of 1416 (0.42%) children had a positive dengue rapid test, while none of the RT-PCR results were positive. ELISA testing demonstrated reactive IgG antibodies in 28 (2.2%) participants with the highest prevalence seen at the urban site in Mbarara (19 of 392, 4.9%, p < 0.001). Conclusions: Overall, these findings suggest that dengue, while present, is an uncommon cause of non-malarial, pediatric febrile illness in western Uganda. Further investigation into the ecological factors that sustain low-level transmission in urban settings are urgently needed to reduce the risk of epidemics
Keywords: Dengue; Fever; Arbovirus; Epidemiology; Uganda